Pemetaan prinsip esensial dan konsep fundamental dari literasi kelautan pada film Avatar: the way of water untuk siswa SMA - Rio Christy Handziko; Wihekan Paramitha; Anggi Tias Pratama; Yuni Wibowo; Tri Asih (Biosfer: Jurnal Pendidikan Biologi, 2026)
Ocean literacy competences are important for Indonesia as an archipelagic country, yet it’s integration into learning remains limited. Popular movie Avatar: The way of water can used as alternative learning media to introduce ocean-related concepts. This research aimed to connect and map the 7 essential principles and 45 fundamental concepts of the ocean literacy in the movie Avatar: The way of water. Type of research conduct was qualitative research with semiotic method that had been done by identified detonative and connotative signs with data sheets concepts map as an instrument. Research had been conducted by identification of scenes, dialogues, and narrations on the whole duration movie. After that, mapping of the key scenes had been done as samples to be analysed. All the scenes, dialogues and narrations be identified for the ocean representation. Then, all the samples been categorized to connect with ocean literacy that had been globally developed by NOAA and UNESCO-IOC. Data had been qualitative analysed by comparison for each scene, dialogue and narration based on principles and concepts of ocean literacy. The results showed that movie of Avatar: The way of water contains 6 essential principles and 11 fundamental concepts of ocean literacy. It means that movie of Avatar: The way of water can be used for learning resource of ocean literacy.